Bupivacaine inhibits endothelin‐1‐evoked increases in intracellular calcium in model sensory neurons. Issue 7 (15th February 2015) - Makdessi, M. J.; Barr, T. P.; Xue, W.; Strichartz, G. R.
<x xml:space="preserve">Abstract</x> Background Endothelin‐1 (ET‐1) induces pain‐like behavior in animals and man by activating the Gq protein‐coupled receptor endothelin‐A (ETA). Activation of ETA receptors on nociceptor membranes evokes intracellular calcium transients and alters membrane Na+ and K+ channel and TRPV1 currents, leading to neuronal hyper‐excitability manifested by spontaneous and evoked pain behaviors in vivo. In addition to blocking sodium channels, local anesthetics inhibit the Gq protein‐coupled signaling of several inflammatory and pro‐algesic mediators. In this study, we aimed to investigate the actions of local anesthetics on ETA‐mediated increases in intracellular calcium in ND7/104 model sensory neurons. Methods Increases in intracellular calcium were measured by the fluorescent indicator fura‐2 in a sensory neuron‐derived cell line (ND7/104), which endogenously expresses ETA receptors. Effects of lidocaine and bupivacaine, along with their respective membrane‐impermeant derivatives QX‐314, LEA‐123 and LEA‐124, on peak calcium responses to ET‐1 were measured. Results Bupivacaine suppressed ET‐1 responses in a concentration‐dependent and non‐competitive manner with an IC50 of 3.79 ± 1.63 mM. Bupivacaine (6 mM) reduced the Emax for ET‐1 from 50.07 ± 1.91 mM to 27.30 ± 2.92 mM. The actions of bupivacaine occurred quickly and were rapidly reversible. Membrane‐impermeant analogs of bupivacaine (LEA‐123 and LEA‐124, 6 mM) were without effect, as was lidocaine (10 mM) and its quaternary derivative QX‐314 (10 mM). Conclusion Bupivacaine inhibits ETA‐mediated calcium transients at clinically relevant concentrations through an intracellular target. The anti‐inflammatory and analgesic actions of bupivacaine may be at least partially due to its inhibitory action on Gq‐coupled receptors, including ETA.